2013
DOI: 10.1155/2013/653471
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic, Psychiatric and Materiality Determinants and Risk of Postpartum Depression in Border City of Ilam, Western Iran

Abstract: Background. Postpartum depression (PPD) is considered as one of the mood disturbances occurring during 2-3 months after delivery. The present study aimed to determine the prevalence of PPD and its associated risk factors in border city of Ilam, western Iran. Methods. Through a descriptive cross-sectional study in 2011, overall, 197 women who attended Obstetrics & Gynecology clinics postpartumly in the border city of Ilam, western Iran, were randomly recruited. A standard questionnaire that was completed by a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 37 publications
3
11
2
2
Order By: Relevance
“…Many studies proposed that, compared to house-wife, employed mothers have been identified to be more at risk for PPDS (Bloch et al, 2005;Taherifard, Delpisheh, Shirali, Afkhamzadeh, & Veisani, 2013). However, this study evidenced no significant relationship between mother's work hours and the trajectories of her postpartum-depressive symptoms, but the relationship had the negative direction.…”
Section: Discussioncontrasting
confidence: 71%
“…Many studies proposed that, compared to house-wife, employed mothers have been identified to be more at risk for PPDS (Bloch et al, 2005;Taherifard, Delpisheh, Shirali, Afkhamzadeh, & Veisani, 2013). However, this study evidenced no significant relationship between mother's work hours and the trajectories of her postpartum-depressive symptoms, but the relationship had the negative direction.…”
Section: Discussioncontrasting
confidence: 71%
“…The Ilam province (where the present study took place) has one of the highest rates of depression and suicide among the 31 provinces in Iran (Taherifard et al, 2013;Veisani et al, 2016). In this study, the aim was to determine the efficacy of diagnosis of psychiatric and mental disorders (based on GHQ questionnaire and DSM-IV-TR classification) and if there were any gender differences.…”
Section: Introductionmentioning
confidence: 83%
“…[5][6][7] The prevalence is different according to population tried and screening instrument put-upon (screening standardized diagnostic tool), the point in the time applied, dissimilar cut off points of the same tool and other ethnic and geographical issues. 8 The diagnostic and statistical manual of mental disorders define PPD as a major depressive episode that take place within four weeks after delivery and this risk may extend for one year. 9 The symptoms of PPD are tearfulness, dependency, and feeling of guilt, insomnia, fatigue, and appetite change.…”
Section: Introductionmentioning
confidence: 99%